The Role Of Product Innovation And Marketing Performance In Enhancing Competitive Advantage In Micro, Small, And Medium Enterprises (MSMEs) In The Fashion Sector - Ratih Indriyani; James Albert Shan (UNIVED Press, 2024)
MSMEs engaged in the fashion sector must have a competitive advantage in overcoming business competition. Competitive excellence cannot be separated from the role of product innovation, digital marketing, and marketing success. This study aims to analyze the influence of product innovation on competitive advantage through marketing performance moderated by digital marketing in the fashion business sector in Surabaya. The type of research used is quantitative research and sampling techniques, namely purposive sampling techniques with the number of samples obtained based on criteria. This study was conducted by distributing questionnaires to as many as 128 respondents. The results showed that product innovation has a significant effect on competitive advantage, product innovation has a significant effect on marketing performance, marketing performance has a significant effect on competitive advantage, product innovation does not have a significant effect on competitive advantage moderated Digital marketing and marketing performance do not have a significant effect on the competitive advantage moderated by digital marketing.